Aggressively delivered mechanism over variable length density using a simulated annealing algorithm in mobile ad hoc network. Issue 12 (26th January 2020) - Sundar, R.; Kathirvel, A.
Abstract: In a mobile ad hoc network, a node moves dynamically without any centralized control. Each node has its autonomous behavior to perform route discovery and packet forwarding. Ad hoc on‐demand distance vectors establish the path, and there may be path loss due to rapid node mobility. When all paths become unavailable, route discovery is done once again, but it may lead to routing overhead and delay in transmission. A novel approach of dynamic clustering mechanism with nondeterministic simulated (DCHA) technique is implemented to avoid path loss and to establish a stable link between the source and the destination. Dynamic clusters are organized along the path based on the local minimum and the global minimum of mobile nodes. So, every problem that you are solving needs to have a way to describe goodness of the solution. Local minimum to applying an algorithm like this to solve the problem is to be careful and check whether sufficient neighbor nodes are available; on the other hand, global minimum is based on the way in which the configuration of systems changes every time during exploitation and exploration. In the proposed algorithm be simulated in NS2 with evaluating through the path stability is maintained and further route discovery is eliminated.